2001
DOI: 10.1002/1099-0682(200109)2001:9<2385::aid-ejic2385>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

New Rhodium(I) and Iridium(I) Complexes of the Chiral 1,1′-Diphenyl-3,3′,4,4′-tetramethyl-2,2′-biphosphole Ligand − Synthesis and Applications to Catalytic Hydrogenation and Hydroformylation Reactions

Abstract: A convenient method for the synthesis of new racemic Rh I and Ir I complexes [M(BIPHOS)(COD)]BF 4 have been developed from the BIPHOS ligand and [M(COD)Cl] 2 precursors. These complexes have been tested as catalysts for hydrogenation and hydroformylation reactions. Excellent re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In a subsequent paper Daran and Balavoine suggested an alternative in order to avoid the tedious chromatographic separation by spontaneous resolution below the epimerization temperature of -60 °C (Scheme 3.5 2 ) [50]. Immediate complexation to a Rh-or Ir(COD)-complex at -90 °C preserved the optical purity of the bis(phospholene).…”
Section: Alkylsubstituted Bis(phospholes) and Bis(phospholenes)mentioning
confidence: 99%
“…In a subsequent paper Daran and Balavoine suggested an alternative in order to avoid the tedious chromatographic separation by spontaneous resolution below the epimerization temperature of -60 °C (Scheme 3.5 2 ) [50]. Immediate complexation to a Rh-or Ir(COD)-complex at -90 °C preserved the optical purity of the bis(phospholene).…”
Section: Alkylsubstituted Bis(phospholes) and Bis(phospholenes)mentioning
confidence: 99%
“…The metals with pertinent references given in parentheses are: Co [118], Cr [78], Fe [8,9,28,34,42,74,119,120,121,122,123], Ga [8], Ge [124], Hf [125], Ir [126,127], Mn [28,74,128,129,130,131], Mo [132], Nd [9], Pb [124], Pd [11,13,17,28,66,67,68,69,70,71,133,134,135,136,137,138,139], Pt [11,28,69,72,133,134,…”
Section: Phospholes As Ligands In Metal Coordination Complexesmentioning
confidence: 99%
“…The reaction of styrene with the CO/H 2 mixture used in hydroformylations was effectively carried out with the complex [Rh(BIPHOS)(COD)]BF 4 [127] where COD is cyclooctadiene and BIPHOS is the 2,2'-biphosphole 48, first used in a complex for catalysis in 1986 [156]. The hydroformylation reaction is shown in Equation 75.…”
Section: Recent Applications Of Phospholesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Thus, most previous studies have been focused on the development of chiral ligands or processes to efficiently produce the desired branched enantioisomer in high optical purity. 3 However, recent progress on the Rh-catalyzed hydroformylation of styrene has revealed that contrary selectivity for linear aldehyde may also be possible through the choice of solvent, 4 latter constitute an important class of anti-inflammatory drugs and the linear aldehyde is widely used for the production of detergents and plasticizers and in organic synthesis as an important intermediate 11 (for example, it can be used as key starting material for the synthesis of enalapril, marketed by Merck & Co. as a drug for lowering blood pressure 12 ). In the literature, 3-arylpropanal is usually obtained indirectly by rather sophisticated and tedious procedures (e.g., by the reduction of trans-cinnamaldehyde 13 or 3-phenylpropionyl chloride or its derivatives 14 or by the oxidation of 3-arylpropanol 15 ), which inhibits its wide applications.…”
mentioning
confidence: 99%